How positive do testimonials on a restaurant website need to be? Impact of positivity of testimonial reviews on customers' decision-making. (January 2023) - Shin, Seunghun; Shin, Hyejo Hailey; Gim, Jaehee
Abstract: This research aims to examine the impact of the positivity of testimonial reviews on customers' decision-making to address conflicting views about testimonial review strategy of a hospitality business: The business needs to display (i) moderately positive reviews to decrease potential customers' skepticism or (ii) extremely positive ones to provide them with a push. With a mixed-method approach, this research compares the effects of moderately positive reviews on customers' perceptions toward the reviews and the restaurants with those of extremely positive ones. The results show that extremely positive reviews are a more strategic choice for testimonial review strategy, indicating that a hospitality business needs to focus on showcasing its strength through testimonial reviews. This research contributes to the literature on online reviews by discussing the unexplored usage of the reviews, thereby confirming that the unique nature of testimonial reviews needs to be considered to explain their impact on customers' decision-making. Highlights: How a hospitality business optimizes the presentation of testimonial online reviews. Impact of the positivity of testimonial reviews on customers' decision-making. Extremely vs. moderately positive testimonial reviews via a mixed-method approach. Extremely positive reviews are more effective in attracting potential customers.